Price Limit and Financial Contagion: Protection or Illusion? The Tunisian Stock Exchange Case - DABBOU, Halim; SILEM, Ahmed (International Journal of Economics and Financial Issues, 2013)
The aim of this paper is to analyze the role of the price limits system to secure the Tunisian stock market against the contagion by the current world-wide crisis. Initially, we try to show that the contagion observed in the Tunisian market is of psychological nature before analyzing the role played by the price limits to avoid a stock exchange crash. Our empirical investigation deals with the behavior of the Tunisian market around the downward price limits. Two methodologies are used: that of Kim and Rhee (1997), become impossible to circumvent in the studies being interested in the price limits and that standard event studies, applied to return and volume. Our results show that the price limits played a stabilizing part in the case of the price falls without undesirable effects, contrary to the results found on several other markets. Keywords: price limits; event studies; financial contagion. JEL Classifications: G01; G14; G15